Blumea sonbhadrensis, a new synonym of Erigeron sublyratus (Asteraceae) - Tiwari, Arjun Prasad; Garg, Arti; Shukla, Achuta Nand (Phytotaxa, 2021)
Our critical examination of the type material and protologue of Blumea sonbhadrensis Narain et al. revealed that this species actually corresponds to Erigeron sublyratus (Astereae), instead of Blumea mollis (Inuleae) as originally supposed. The species is therefore resolved here as a synonym of Erigeron sublyratus.